SOLUSI NUMERIK PERSAMAAN BOLTZMANN - NUGRAHANI, E. H. (MILANG Journal of Mathematics and Its Applications, 2003)
Particle methods are well known tools to solve the kinetic Boltzmann equation numerically. The usual procedure of such method is the direct simulation Monte-Carlo, which directly simulate the collision between particles. The second method of interest is the stochastic weighted particle method, which is developed to improve the previous method. The main idea of the second method is to use random weight transfer between particles during collisions. In order to reduce the stochastic fluctuations, this method provides a way to increase the number of particles. But if the additional particles cannot be compensated in some natural way, then this number should be reduced. Several reduction procedures have been proposed. Some numerical results using both methods are presented. It is shown that the second method gives some better results in some ways.